Dual antiplatelet therapy with 3rd generation P2Y12 inhibitors in STEMI patients: impact of Body Mass Index on high on-treatment platelet reactivity. (14th October 2021) - Scudiero, F; Canonico, M E; Sanna, G D; Saba, P G; Esposito, G; Parodi, G
Abstract: Background: High on-treatment platelet reactivity (HTPR) has been associated with high risk of ischemic events in STEMI patients. Body mass index (BMI) and specifically overweight and obesity are risk factors for increased platelet reactivity in different series of patients, however data regarding their relationship with pharmacodynamic response to oral 3rd generation P2Y12 inhibitors is still lacking. Purpose: This study aims to assess the association between BMI and HTPR in STEMI patients treated with oral 3rd generation P2Y12 inhibitors. Methods: Overall, 429 STEMI were enrolled in this study. Patients were divided into two groups according to BMI (BMI <25; BMI ≥25). A propensity score matching (1:1) was performed to balance potential confounders in baseline study characteristics. Platelet reactivity was assessed by VerifyNow at baseline and after 3rd generation P2Y12 inhibitor (ticagrelor or prasugrel) loading dose (LD). Blood samples were obtained at baseline (T0), 1 hour (T1), 2 hours (T2), 4–6 hours (T3) and 8–12 hours (T4) after the LD. HTPR was defined with a platelet reactivity unit values ≥208 units. Results: The mean age of the enrolled population was 62±12 and male rate was 75%. Patients with a BMI ≥25 were younger (61±12 Vs 64±11, p=0.006), with a higher prevalence of male gender (78% vs 68%, p=0.035), and hypertension (56% vs 46%, p=0.072), and they were less frequently treated with pre-PCI mophine use (30% Vs 42%; p=0.018). After propensity score matching (Table), patients with BMI ≥25 had similar values of baseline platelet reactivity [T0: 308 (285–342) vs 300 (281–330), p=0.396), while they had higher level of platelet reactivity at 1 and 2 hours after the LD [T1: 285 (200–308) vs 265 (196–320), p=0.047); T2: 241 (87–305) vs 200 (56–256), p=0.004)] and higher rate of HRPT [T1: (66% vs 47%, p=0.004); T2: (40% vs 24%, p=0.006)]. Furthermore, multivariable analysis demonstrated that BMI ≥25 was an independent predictor of HTPR at 2h (OR 2.01, 95% CI 1.18–3.42; p=0.009). Conversely, starting from 4 hour after the LD, platelet reactivity values [T3: 68 (7–173) vs 15 (6–71), p=0.76); T4: 38 (4–104) vs 44 (4–82), p=0.958)] and HRPT rates (T3: 13% vs 10%, p=0.595; T4: 1% vs 1%, p=0.320) were comparable among the study groups. Conclusions: A BMI ≥25 is associated with decelerated pharmacodynamic response to oral 3rd generation P2Y12 inhibitors LD and resulted a strong predictor of HRPT in STEMI patients treated by dual antiplatelet therapy with ticagrelor or prasugrel. FUNDunding Acknowledgement: Type of funding sources: None.